Microscopy simple or advance technique of material characterization - Obondo, Benard Odhiambo; Nyangoye, Benard Oloo (Open Science Journal, 2019)
Optical microscopy with respect to advanced scientific research can be referred to as the basic techniques for the characterization of materials. Optical microscopy is expected to remain useful in the science world for a long time. Despite being presumed a basic tool, it is capable of giving very detailed information that reveals a lot about the materials preparations, heat treatment prior to observation, defects in the material as well as alloy composition. Relatively hard metals such as titanium, tungsten and steels are easy to prepare for microscopic examination unlike soft materials such as tin and aluminum that pose serious challenges during their preparation leading to defects such as deep scratch lines, embedded abrasive particles, dust particles, as well as water marks covering the polished surface. The material used in this study Cu50Ti25Zr15Ni10 was produced by arc melting. The alloy ingots were re-melted at least 4 times for homogenization of the master alloy. The alloy ingot was then suction cast into a 3mm rod. The alloy metals used for the ingots had purities greater than 99.9% and were purchased from Zhongnuo Advanced Materials (Beijing) Technology Co. Ltd China. The objective of this work was to show the importance of proper and correct specimen preparation in revealing the basic and detailed information concerning the structure, as well as its morphology. A perfectly ground and polished surface is free from defect arising from preparation method hence the presumption that microscopy is a basic science does since even advanced structures can be revealed. It is imperative that a good quality optical microscope be purchased especially when resources are scarce and advanced materials characterization techniques are not available. In can be concluded that with a good quality optical microscope, microscopy as a technique will continue to play a critical role during decision making and that a polished surface will only give accurate information about a given specimen if all preparation stages and steps are taken into consideration, adhered to and carefully and professionally done.